(untitled) (Research, Society and Development, 2020)
This study aimed to verify the level of physical fitness, body image and school performance in students of the initial grades of elementary school. The sample consisted of 285 students selected voluntarily in five municipal schools in the city of Guarapuava/Paraná/Brasil. All participants were students in the fourth and fifth years of elementary school and were aged between eight and eleven years. The instrument used for the verification of physical fitness was the battery of tests "Projeto Esporte Brasil (PROESP-Br)" and for the assessment of body image perception the scale of silhouettes proposed by Kakeshita et al., (2009). School performance was obtained by the average grade of the disciplines that make up the students’ curriculum and later divided into concepts. After the analysis, the results showed that the majority of students, regardless of age and sex, had low levels of physical fitness, both related to health and associated with motor performance. When exploring the impact of physical fitness on school performance, no direct relationship was observed. The same was noticed when the association between body image and school performance was carried out, in which there were no associations, although students with lower grades were more dissatisfied in relation to thinness.